The Private Student's Junior High School and Their Numeracy Literacy Competency - Safira Fitrianingrum; Budi Murtiyasa (Jurnal Penelitian Pendidikan IPA, 2023)
Numerical literacy is an important aspect of schooling. Students must be able to count, relate, and perform arithmetic. The purpose of this study is to know deeply the numeracy literacy competency of private student’s junior high school. The following findings are the result of research employing tests as a data collection instrument. There are two students in the high category, five in the medium group, and nineteen in the low category. Based on these findings, it is possible to conclude that children at the research school have poor literacy skills. Furthermore, it is envisaged that schools will seek alternate learning techniques capable of concretizing numeracy literacy principles. Numerical literacy is an important part of the world of education. Students are expected to understand and acquire the competency of numeracy.